There is a need to better take into account forest soils in the planned soil monitoring law of the European Union - Wellbrock, Nicole; Cools, Nathalie; de Vos, Bruno; Jandl, Robert; Lehtonen, Aleksi; Leitgeb, Ernst; Mäkipää, Raisa; Pavlenda, Pavel; Schwärtzel, Kai; Šrámek, Vít (BioMed Central, 2024)
Key message A Soil Monitoring Law to improve soil health across all land uses has been proposed by the European Commission. As forests soils have different chemical and physical properties as well as biogeochemical dynamics compared to agricultural land, they also face different challenges in maintaining and restoring soil health. Examples are soil acidification, eutrophication by atmospheric deposition, responses to climate change, and loss of biodiversity. Therefore, we propose forest soil specific health descriptors and thresholds based on experience and knowledge from existing long-term monitoring programs.
Keywords: forest soil monitoring; ICP forests; soil health; forest floor; tresholds; indicators